ANALISIS PERUBAHAN SUHU PERMUKAAN KOTA MEDAN PRA DAN POST PANDEMI COVID-19 - Omeria Waruwu (Geography Education Study Program, Universitas Samudra, 2022)
Corona viruses are a large family of viruses that can cause disease in animals or humans. In humans, corona is known to cause respiratory infections ranging from the common cold to more severe diseases such as Middle East Respirator syndrome (MERS) and Severe Acute Respirator syndrome (SARS). The temperature transformation was carried out using the Land Surface Temperature (LST) method, the SEBAL (Surface Energy Balance Algorytms for Land) method to assess the temperature in the landsat imagery before and after the COVID-19 pandemic. In this study, the LST identification process was carried out using ENVI 5.1 software and making layouts. map using ArcGIS 10.7 software. The SEBAL LST method uses the Band Match equation (B6/1) + (B7*(B6/1438)) * (alog(B8)), using Landsat imagery for the March 2020 period for the period before the COVID-19 pandemic and Landsat image data for the October 2021 period after the covid-19 pandemic in the city of Medan.